FAKTOR FAKTOR YANG MEMPENGARUHI INDEPENDENSI AUDITOR DI JAWA TENGAH (Studi Empiris pada Kantor Akuntan Publik di Jawa Tengah) - Brilian Akbar Rakai A.W.S; Andi Kartika (Dinamika Akuntansi Keuangan dan Perbankan, 2015)
This research was motivated by the behavior of auditors in auditing the financial report of clients. The purpose of this study is to examine the effect of the bond financial interests and business relationships with clients, management advisory services (MAS), tenure of audit, the competition of audit firm, size of audit firm, and size of audit fees received by audit firm toward auditor’s independence in Central Java.The population of this study is public accounting firm in Central Java that was registered in Otoritas Jasa Keuangan (OJK) on December 31, 2015 .Sampling was done using purposive sampling method. The sample of this study was 14 audit firm (KAP) and the amount of respondents was 72. The primary data collection method were by a questionnaire method. Mail-survey were done to audit firms that were located in Purwokerto, while direct survey were done to audit firms that were located in Solo and Semarang.Data were analyzed using multiple linier regression model. The result reveales a positive significant relationship between the variables of; bond financial interest and bussiness relationships with client, size od audit firm, and size of audit fees received by audit firms to auditor’s independence, while management advisory services (MAS), tenure of audit,and the competition of audit has no significant affect toward auditor’s independence.     Keywords:    The bond financial interests and business relationships with clients, management advisory services (MAS), tenure of audit, the competition of audit firm, size of audit firm, size of audit fees received by audit firm, and auditor,s independence.